Prevalence and characterization of influenza viruses in diverse species in Los Llanos, Colombia. (2013)
While much is known about the prevalence of influenza viruses in North America and Eurasia, their prevalence in birds and mammals in South America is largely unknown. To fill this knowledge gap and provide a baseline for future ecology and epidemiology studies, we conducted 2 years of influenza surveillance in the eastern plains (Los Llanos) region of Colombia. Real-time reverse transcriptase polymerase chain reaction (RT-PCR) identified influenza viruses in wild birds, domestic poultry, swine and horses. Prevalence ranged from 2.6% to 13.4% across species. Swine showed the highest prevalence and were infected primarily with 2009 pandemic H1N1 (pH1N1) viruses genetically related to those in humans. In addition, we isolated H5N2 viruses from two resident species of whistling ducks (genus Dendrocygna) that differed completely from previous South American isolates, instead genetically resembling North American wild bird viruses. Both strains caused low pathogenicity in chickens and mammals. The prevalence and subtype diversity of influenza viruses isolated from diverse species within a small area of Colombia highlights the need for enhanced surveillance throughout South America, including monitoring of the potential transmissibility of low-pathogenic H5N2 viruses from wild birds to domestic poultry and the emergence of reassortant viruses in domestic swine.